1995
DOI: 10.1071/ar9950703
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for terminal sires estimated using data of progeny from Border Leicester × Merino ewes

Abstract: Three and a half thousand lambs from Border Leicester x Merino ewes mated to 133 sires from five Poll Dorset, one White Suffolk, one Siromt, two Meridale and four Merino studs were slaughtered, their carcasses halved and one side divided into six primals. Subcutaneous fat was dissected from all six primals, and bone from only the three rear primals. There were four slaughter groups: average slaughter weights of 30 and 35 kg for ewes and 35 and 45 kg for cryptorchids. Heritabilities and phenotypic and genetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
3
6
0
Order By: Relevance
“…These studies also reported estimates close to zero for post-weaning weight with FATGR and FATC (Ingham et al 2007) and scanning weight with FATC, but not FATGR (0.33) (Greeff et al 2008). Kenney et al (1995) reported a genetic correlation of 0.65 between hind-leg bone weight and weaning weight, which is consistent with the estimate (0.76) in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These studies also reported estimates close to zero for post-weaning weight with FATGR and FATC (Ingham et al 2007) and scanning weight with FATC, but not FATGR (0.33) (Greeff et al 2008). Kenney et al (1995) reported a genetic correlation of 0.65 between hind-leg bone weight and weaning weight, which is consistent with the estimate (0.76) in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…For the genetic correlations involving the carcass muscle dimensions, the stronger genetic correlations (greater than~0.3 in size) were for EMW with WWT, WTUS and FATUS, for EMD with EMDUS and FATUS and for EMA with FATUS. The preliminary estimates of these genetic relationships were similar to the estimates reported by Kenney et al (1995), Ingham et al (2007) and Greeff et al (2008). The high positive genetic correlations of EMDUS with EMD and EMA were very similar to estimates reported by Greeff et al (2008) (0.82 and 0.63, respectively).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Heritability estimates have been moderate to high from the relatively few studies that have estimated genetic variances for carcass dissection traits in sheep, with our results consistent with those earlier estimates. These earlier reports for heritability include 0.36 for WTLL and 0.37 for total lean (Waldron et al, 1992), 0.27 ± 0.06 for meat in 3 primal cuts (Kenney et al, 1995), 0.27 ± 0.11 for lean in the shoulder (Conington et al, 1998), 0.41 for WTLL and 0.24 to 0.31 for lean in various other cuts (Johnson et al, 2006), 0.46 for lean in the carcass (van Heelsum et al, 2006), 0.37 for lean in the loin (Jopson et al, 2009), and 0.32 ± 0.14 for WTLL and 0.24 ± 0.14 for WTTOP (Lorentzen and Vangen, 2012). There have also been other studies reporting heritabilities of 0.2 to 0.5 for lean using video image analysis (Rius-Vilarrasa et al, 2009;Einarsson et al, 2015;Johnson et al, 2015a,b) and computer tomography (CT; Jones et al, 2004;Karamichou et al, 2006;Kvame and Vangen, 2007;Lambe et al, 2008) procedures.…”
Section: Heritabilitymentioning
confidence: 92%